this is easy but i’m having a bad day and this is almost due please help i will give brainliest
![this is easy but im having a bad day and this is almost due please help i will give brainliest class=](https://us-static.z-dn.net/files/d76/a9475fbc86c226c01d72917d65f6a808.png)
Answer:
Step-by-step explanation:
okay so if we lay it out...,
f(x) 6-5x x-9 x³ 2x-5 12x+3
f(-3) 21 12 -27 -11 -33
f(-2) 16 -11 -8 -9 -21
f(0) 6 -9 1 -5 3
f(1) 1 -8 1 -3 15
f(2) -4 -7 8 -1 27
okay so the left side is all the f(x) values. So the numbers in the "()" represents "x". Now you just substitute the numbers in the"()" for the "x"'s on the top margins. so...,
f(-3)= 6-5x f(-2)= 6-5x f(0)=6-5x f(1)=6-5x f(2)=6-5x
f(-3)= 6-5(-3) f(-2)= 6-5(-2) f(0)=6-5(0) f(1)=6-5(1) f(2)=6-5(2)
f(-3)= 6+15 f(-2)= 6+10 f(0)=6-0 f(1)=6-5 f(2)=6-10
f(-3)= 21 f(-2)= 16 f(0)=6 f(1)= 1 f(2)= -4
f(-3)=x-9 f(-2)=x-9 f(0)=x-9 f(1)=x-9 f(2)=x-9
f(-3)=(-3)-9 f(-2)=(-2)-9 f(0)=0-9 f(1)=1-9 f(2)=2-9
f(-3)=-12 f(-2)=-11 f(0)= -9 f(1)= -8 f(2)= -7
f(-3)=x³ f(-2)=x³ f(0)=x³ f(1)= x³ f(2)=x³
f(-3)=(-3)³ f(-2)= (-2)³ f(0)=0³ f(1)=1³ f(2)=2³
f(-3)= -27 f(-2)= -8 f(0)= 1 f(1)= 1 f(2)=8
f(-3)= 2x-5 f(-2)= 2x-5 f(0)= 2x-5 f(1)= 2x-5 f(2)=2x-5
f(-3)=2(-3)-5 f(-2)=2(-2)-5 f(0)= 2(0)-5 f(1)= 2(1)-5 f(2)=2(2)-5
f(-3)= -6-5 f(-2)= -4-5 f(0)=0-5 f(1)=2-5 f(2)=4-5
f(-3)= -11 f(-2)= -9 f(0)= -5 f(1)= -3 f(2)= -1
f(-3)=12x+3 f(-2)=12x+3 f(0)=12x+3 f(1)=12x+3 f(2)=12x+3
f(-3)= 12(-3)+3 f(-2)=12(-2)+3 f(0)=12(0)+3 f(1)=12(1)+3 f(2)=12(2)+3
f(-3)= -36+3 f(-2)= -24+3 f(0)= 0+3 f(1)=12+3 f(2)=24+3
f(-3)= -33 f(-2)= -21 f(0)=3 f(1)=15 f(2)= 27
Don't know if you wanted all the work. But I just did it for you so you can see.